2016
DOI: 10.1111/plb.12521
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of endophytic bacteria in the halophyte Arthrocnemum macrostachyum salt tolerance

Abstract: There is an increasing interest to use halophytes for revegetation of salt affected ecosystems, as well as in understanding their mechanisms of salt tolerance. We hypothesized that bacteria from the phyllosphere of these plants might play a key role in its high tolerance to excessive salinity. Eight endophytic bacteria belonging to Bacillus and closely related genera were isolated from phyllosphere of the halophyte Arthrocnemum macrostachyum growing in salty agricultural soils. The presence of plant-growth pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 50 publications
6
29
0
Order By: Relevance
“…Recently, increasing attention has focused on the utilization of microbes to mediate plant salt tolerance [31][32][33]. Previous studies have shown that endophytic bacteria associated with halophytic plants invariably show high salt tolerance and play important roles in the salt tolerance of host plants [34][35][36]. Consistently, Rejili et al reported that rhizobia in the nodules of wild legumes growing in saline soils showed salt tolerance [37].…”
Section: Discussionmentioning
confidence: 92%
“…Recently, increasing attention has focused on the utilization of microbes to mediate plant salt tolerance [31][32][33]. Previous studies have shown that endophytic bacteria associated with halophytic plants invariably show high salt tolerance and play important roles in the salt tolerance of host plants [34][35][36]. Consistently, Rejili et al reported that rhizobia in the nodules of wild legumes growing in saline soils showed salt tolerance [37].…”
Section: Discussionmentioning
confidence: 92%
“…A large number of reports have shown that halotolerant plant growth-promoting rhizobacteria (PGPRs) isolated from halophytes enhance salt tolerance in their host plants. For example, the salt tolerance of Arthrocnemum macrostachyum is improved by its endophytic bacteria ( Navarro-Torre et al, 2017 ; Tian and Zhang, 2017 ). As another example, in Salicornia strobilacea , rhizospheric bacteria which can stably colonize the rhizoplane are capable of improving plant growth ( Marasco et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of endophytic bacteria from halophytes have been shown the ability to improve salt tolerance of their host plants. For example, Navarro-Torre et al (2017) reported that the endophytic bacteria from Arthrocnemum macrostachyum could improve its salt tolerance. Hashem et al (2016) revealed that the growth promotion effect of endophytic bacteria and arbuscular mycorrhizal fungi (AMF) on Acacia gerrardii under salt stress were associated to a tripartite mutualistic symbiosis in A. gerrardii .…”
Section: Introductionmentioning
confidence: 99%